Examining motivations influencing watershed partnership participation in the Intermountain Western United States. Issue 107 (May 2020) - Roberts, Ryan M.; Jones, Kelly W.; Cottrell, Stuart; Duke, Esther
Highlights: Analysis revealed six distinct perspectives that drive organizations to participate. The first perspective, Environmental Mission, explains 48 % of the study variance. Internal motivations play a stronger role in participation than external pressures. Knowledge about motivations can aid future watershed partnerships. Abstract: There has been a rise in environmental collaboratives as a form of watershed governance. These collaboratives depend on a diversity of organizations acting collectively by pooling their resources, yet little information exists as to why organizations decide to become involved in these initiatives. This study attempts to identify why organizations involved in watershed partnerships decide to participate by assessing external and internal motivations. We used Q method to survey 38 representatives from 32 organizations currently participating by investing time or resources in these partnerships in the Intermountain Western United States. Factor analysis revealed six distinct perspectives organizations hold that influence their decision to participate. Our findings differ from the broader environmental management literature in that internal motivations played a much larger role in organizations' motivations for participation. Specific categories of internal motivations that were important included: 1) Environmental Mission, 2) Environmental Leadership, and 3) Wildfire Information. Results suggest that diverse strategies are needed to engage potential partner organizations in watershed collaboratives.